When conflict influences liking: The case of the Stroop task. - Tom G E Damen; Madelijn Strick; Toon W Taris; Henk Aarts (PLoS ONE, 2018)
Research suggests that cognitive conflict is accompanied by a negative signal. Building on the demonstrated role of negative affect in attitude formation and change, the present research investigated whether the experience of cognitive conflict negatively influences subsequent evaluations of neutral stimuli. Relying on the emergence of conflict in the Stroop task, participants were presented with compatible (non-conflict) and incompatible (conflict) Stroop color words that were each followed by a neutral visual stimulus. In general, participants liked stimuli following incompatible Stroop words less than stimuli following compatible Stroop words. The results revealed similar compatibility effects in tasks in which participants actively responded to the Stroop words and in tasks in which they passively observed them. Furthermore, these effects emerged in offline and online measures of evaluation. Interestingly, the results also suggest that the compatibility effect on liking observed in the present research was to some degree driven by the positivity associated with the compatible Stroop words, and not just by the negativity associated with the incompatible Stroop words. We discuss the present findings in the context of how and when conflicting responses to events (such as in the Stroop task) can influence evaluations of stimuli associated with the conflicting events.